An fNIRS Study of Brain Lateralization During Observation and Execution of a Fine Motor Task - Khaksari, Kosar; Smith, Elizabeth G.; Miguel, Helga O.; Zeytinoglu, Selin; Fox, Nathan; Gandjbakhche, Amir H. (Frontiers in Human Neuroscience, 2022)
Brain activity in the action observation network (AON) is lateralized during action execution, with greater activation in the contralateral hemisphere to the side of the body used to perform the task. However, it is unknown whether the AON is also lateralized when watching another person perform an action. In this study, we use fNIRS to measure brain activity over the left and right cortex while participants completed actions with their left and right hands and watched an actor complete action with their left and right hands. We show that while activation is lateralized when the participants themselves are moving, brain lateralization is not affected by the side of the body when the participant is observing another person’s action. In addition, we demonstrate that individual differences in hand preference and dexterity between the right and left hands are related to brain lateralization patterns.